Peningkatan Pemahaman Materi Fiqih melalui Model Pembelajaran Langsung pada Siswa Madrasah Ibtidaiyah - Mahfut Amrullah (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2023)
This study aims to determine the effectiveness of the implementation of direct learning models in improving the understanding of Fiqh material in elementary school students. This study uses a Classroom Action Research (CAR) approach which is implemented in two cycles, each consisting of planning, implementation, observation, and reflection stages. The direct learning model was chosen because of its systematic and structured approach, which is considered capable of helping students understand Fiqh material which tends to be considered difficult and abstract. The results of the study showed a significant increase in student understanding, both in terms of academic test results and activeness in class discussions. This model not only helps students understand the basic concepts of Fiqh, but also encourages them to relate the material to everyday life practices. Although challenges are still found, especially in delivering more complex Fiqh material, the implementation of direct learning generally has a positive impact on the quality of Fiqh learning at MI Nurul Yaqin Donoyudan.